2021
DOI: 10.1101/2021.11.22.469574
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlations from structure and phylogeny combine constructively in the inference of protein partners from sequences

Abstract: Inferring protein-protein interactions from sequences is an important task in computational biology. Recent methods based on Direct Coupling Analysis (DCA) or Mutual Information (MI) allow to find interaction partners among paralogs of two protein families. Does successful inference mainly rely on correlations from structural contacts or from phylogeny, or both? Do these two types of signal combine constructively or hinder each other? To address these questions, we generate and analyze synthetic data produced … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 95 publications
(229 reference statements)
0
12
0
Order By: Relevance
“…Note that, in Ref. [32], we showed that these pairs of sites are particularly useful for the inference of interacting partners among the paralogs of two protein families, where phylogenetic correlations are useful.…”
Section: Resultsmentioning
confidence: 99%
“…Note that, in Ref. [32], we showed that these pairs of sites are particularly useful for the inference of interacting partners among the paralogs of two protein families, where phylogenetic correlations are useful.…”
Section: Resultsmentioning
confidence: 99%
“…While unifying these two signals in a single framework remains a hard problem, they have been shown to combine constructively in the inference of protein partners among paralogs by coevolution methods [24], raising the possibility that explicitly combining them may further increase performance. Here, we combine these two signals in a technically straightforward way.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the limited numbers of paralogs per species in these datasets make the IPA already very efficient and robust without any seed co-MSA. Note that the successful performance of IPA on pairs of protein families with no known interaction shows that it is already able to exploit phylogenetic signal [23,24]. With GA, this signal is exploited more explicitly.…”
Section: Using a Robust Partial Co-msa To Seed The Coevolution-based ...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, as bmDCA and MSA Transformer are trained on natural data, they can capture phylogenetic correlations [53]. Besides, inferred Potts models are known to be impacted by phylogenetic correlations [8,10,[65][66][67][68][69][70][71].…”
Section: Msa Transformer Captures Well the Distribution Of Sequences ...mentioning
confidence: 99%